The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14218/jcth.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Case Control Study of Post-endoscopic Variceal Ligation Bleeding Ulcers in Severe Liver Disease: Outcomes and Management

Abstract: Background and Aims: The management of post-endoscopic variceal ligation (EVL) bleeding ulcers (PEBUs) is currently based on local expertise and patients liver disease status. The present retrospective study investigated associations between the endoscopic morphology of PEBUs and patient outcomes. Methods: Patients underwent EVL (primary or secondary), from January 2015 to January 2018, in two tertiary care hospitals in India (ILBS New Delhi and Dharamshila Narayana New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…The pooled incidence of early post-EVL bleeding was 7.7% (95% CI: 6.1-9.3, I 2 = 91.9%) with data from 16 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Fig. 2).…”
Section: Incidence Of Early Bleeding After Evlmentioning
confidence: 93%
See 2 more Smart Citations
“…The pooled incidence of early post-EVL bleeding was 7.7% (95% CI: 6.1-9.3, I 2 = 91.9%) with data from 16 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Fig. 2).…”
Section: Incidence Of Early Bleeding After Evlmentioning
confidence: 93%
“…A total of 879 records were identified, out of which 794 were screened after removal of duplicates. Thirty reports were assessed for eligibility and 16 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were included in the final analysis. Figure 1 outlines the detailed search strategy as per the PRISMA guidelines.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…coagulopathy (increased PT, INR and low platelets) 3. post EVL band ulcers (PEBU's), 4. slippage of bands or 5. presence of SRH (stigmata of recent hemorrhage -platelet plug, ulcer) or RCS (red color signs -red wale signs, cherry red spots) [2][3][4].…”
mentioning
confidence: 99%
“…The management in this group of patients depends upon the general condition of the patient and the underlying liver disease status. There was a recent study which showed that endoscopic appearance of post banding ulcers can determine the patient outcomes in addition and independent to MELD-Na score [4]. It is a combined team effort involving a hepatology, diagnostic radiology, intervention radiology and a liver transplant team.…”
mentioning
confidence: 99%